1991
DOI: 10.2118/20208-pa
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Cyclic CO2 Injection for Light-Oil Recovery

Abstract: Summary Field performance trends are presented for cyclic CO2 injection light-oilsandstone reservoirs. Results indicate that the mass of CO2 injected is thebest predictor of stimulated oil prod uction rate and ultimate incrementalrecovery. The correlations prod uction rate and ultimate incremental recovery. The correlations enhance understanding of the single-well process, improvereservoirs election criteria, and suggest operational guidelines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…In practice, after the gas injection, the well is shut-in for a period of time to allow for intense gas-oil interaction. It was reported that extending the soak period up to 4 weeks significantly improved the production response [21]. However, this period cannot be excessively long because it could cause the pressure dispersion in the reservoir that leads to re-release of dissolved gas, and because the CO 2 would dissipate due to compositional gradient leading to reduced CO 2 concentration in the oil.…”
Section: Gas Diffusion and Mass Transfermentioning
confidence: 99%
“…In practice, after the gas injection, the well is shut-in for a period of time to allow for intense gas-oil interaction. It was reported that extending the soak period up to 4 weeks significantly improved the production response [21]. However, this period cannot be excessively long because it could cause the pressure dispersion in the reservoir that leads to re-release of dissolved gas, and because the CO 2 would dissipate due to compositional gradient leading to reduced CO 2 concentration in the oil.…”
Section: Gas Diffusion and Mass Transfermentioning
confidence: 99%
“…Thomas and Monger-McClure (1991) evaluated performance trends for light-oil cyclic C02 stimulation treatments and suggested the following well selection guidelines q Desirable reservoir characteristics include shallower reservoirs, operating below the minimym miscibility pressure, a thick pay interval, a mobile-water or free-gas saturation, and an adequate drive mechanism.…”
Section: D9i Screening Criteriamentioning
confidence: 99%
“…Almost all the CO2 EOR projects in Permian Basin have been designed as miscible or near miscible processes. CO2 injection schemes have evolved from huff n' puff (or cyclic) injection [3] to Tapered Water Alternating Gas (TWAG) injection [2] . Table 1 summaries the major injection schemes developed in the last 30+ years [4,5,6,7,8,9] .…”
Section: Introductionmentioning
confidence: 99%